On the Normalization of Toponyms with Varying ы [y] / и [i] after ц [ts] - I. A. Dambuev (Научный диалог)
The article is devoted to the study of the variation of the letters ы [y] and и [i] after ц [ts] in toponyms ending in -цыно(а) / -цино(а) , -цынск- / -цинск- , as well as the normalization of such toponyms at the present stage. The relevance of the study is due to the need to create common principles for the normalization of place names and improve the rules of Russian spelling. The novelty of the study is seen in the use of linguistic and statistical methods on the material of the entire Russian toponymicon. On the basis of the State catalog of geographical names, legal acts, topographic maps and directories of the administrative-territorial structure, examples of variable toponyms are revealed and the features of their normalization are shown. A historical review of the codified use norm on the letter ы and и after ц is completed. Using statistical analysis, it was found that almost half of the toponyms are written contrary to the current spelling rules. The results of the analysis of the usual spelling of the considered toponyms of different regions over the past half century are presented. The principle of traditional spelling of geographical names is called into question. A case has been revealed in the spelling of geographical names that does not have a codified norm. Suggestions have been made to improve the normalization of place names ending in -цыно(а) / -цино(а) , -цынск- / -цинск- .